Parametrically Sufficient Optimality Conditions for Multiobjective Fractional Subset Programming Relating to Generalized (η, ρ, θ)-Invexity of Higher Order - Verma, Ram U. (Journal of Informatics and Mathematical Sciences, 2013)
Inspired by the recent investigations, a general framework for a class of (η, ρ,θ)-invex n-set functions of higher order r≥ 1 is introduced, and then some optimality conditions for multiobjective fractional programming on the generalized (η,ρ,θ)-invexity are established. The obtained results are general in nature and unify various results on fractional subset programming in the literature.